Mindfulness- and Acceptance-based Interventions for Psychosis: A Systematic Review and Meta-analysis - Cramer, Holger (Glob Adv Health Med, 2016)
BACKGROUND: Mindfulness- and acceptance-based interventions are increasingly studied as a potential treatment for a variety of mental conditions. OBJECTIVE: To assess the effects of mindfulness- and acceptance-based interventions on psychotic symptoms and hospitalization in patients with psychosis METHODS: MEDLINE/PubMed, Embase, the Cochrane Library, and PsycINFO were screened from inception through April 2015. Randomized controlled trials (RCTs) were analyzed when they assessed psychotic symptoms or hospitalization in patients with psychosis; affect, acceptance, mindfulness, and safety were defined as secondary outcomes. RESULTS: Eight RCTs with a total of 434 patients comparing mindfulness-based (4 RCTs) or acceptance-based interventions (4 RCTs) to treatment as usual or attention control were included. Six RCTs had low risk of bias. Moderate evidence was found for short-term effects on total psychotic symptoms, positive symptoms, hospitalization rates, duration of hospitalization, and mindfulness and for long-term effects on total psychotic symptoms and duration of hospitalization. No evidence was found for effects on negative symptoms, affect, or acceptance. No serious adverse events were reported. CONCLUSION: Mindfulness- and acceptance-based interventions can be recommended as an additional treatment for patients with psychosis.